Synthesis and Anti-inflammatory Activity of Some New 6-Aryltriazolo[3,4-b][1,3,4]thiadiazole Derivatives - Iryna I. Myrko (Журнал органічної та фармацевтичної хімії)
A series of 6-aryl[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole derivatives has been synthesized. Their anti-inflammatory activity has been studied in vivo in a carrageenan model of the paw inflammatory edema in rats. 3-(2-Fluorophenyl)-6-phenyl-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole (3c) and 3-(2-fluorophenyl)-6-(4-methoxy-phenyl)[1,2,4]triazolo[3,4-b][1,3,4]thiadiazole (3d) have been identified as hit compounds with the anti-exudative activity. The crucial role of the fluorine atom in the anti-inflammatory activity has been determined, which value considerably correlates with the calculated values of lipophilicity and solubility.